PERANCANGAN ELECTRONIC CUSTOMER RELATIONSHIP MANAGEMENT PADA AGOONG CELL BERBASIS WEB (Information Technology and Telematics, 2014)
Abstract - - At the writing of this thesis, discusses how to make the application of E-CRM. Currently the implementation of applications an upper middle corporate institutions must meet the concept of developing an easy and reusable.Sering the redesign process in an enterprise application, due to the development of software applications that are not reusable and are relatively difficult. This resulted in a loss for some companies because of the cost of development is relatively expensive. The purpose of this study is to design and create the E-CRM so that data collection can facilitate the sale of goods to be more integrated and computerized, this system built using the PHP programming language and MySQL database and coding using Adobe Photoshop CS3 and Dreamweaver 8. From the results of this research, it can be concluded that the process of ordering goods, payment confirmation, as well as testimonials from customers online and computerized lasted well. Keywords: : E-CRM, AGOONG CELL, PHP, MySQL   Abstraksi - Pada Penulisan Tugas akhir ini, membahas tentang bagaimana cara membuat aplikasi E-CRM. Saat ini penerapan aplikasi sebuah lembaga perusahaan menengah ke atas harus memenuhi konsep pengembangan yang mudah dan reusable.Sering terjadinya proses rancang ulang aplikasi di suatu perusahaan, disebabkan adanya pengembangan aplikasi perangkat lunak yang tidak reusable dan relatif sulit. Hal ini mengakibatkan kerugian bagi sebagian perusahaan karena biaya pengembangan yang relatif mahal. Tujuan dari penelitian ini yaitu merancang dan membuat E-CRM sehingga dapat mempermudah pendataan penjualan barang agar lebih terintergrasi dan terkomputerisasi, sistem ini di bangun menggunakan bahasa pemrograman PHP dan database MySQL dan coding menggunakan Adobe Photoshop CS3 serta Dreamweaver 8. Dari hasil penelitian tugas akhir ini, dapat disimpulkan bahwa proses pemesanan barang,konfirmasi pembayaran, serta testimoni dari pelanggan berlangsung secara online dan terkomputerisasikan dengan baik. Kata Kunci : E-CRM, AGOONG CELL, PHP, MySQL